2016
DOI: 10.3389/fpsyg.2016.00913
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Computer-Based Training Program for Enhancing Arithmetic Skills and Spatial Number Representation in Primary School Children

Abstract: Calcularis is a computer-based training program which focuses on basic numerical skills, spatial representation of numbers and arithmetic operations. The program includes a user model allowing flexible adaptation to the child's individual knowledge and learning profile. The study design to evaluate the training comprises three conditions (Calcularis group, waiting control group, spelling training group). One hundred and thirty-eight children from second to fifth grade participated in the study. Training durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 64 publications
(107 reference statements)
0
4
0
2
Order By: Relevance
“…It is assumed that the training leads to a higher automation of task processing resulting in faster fact retrieval. Compared to the evaluative studies regarding the previous version Calcularis 1.0 ( Käser et al, 2013a ; Rauscher et al, 2016 ; Kohn et al, 2017 ) the observed training effects are stronger, whereby it has to be considered that Calcularis 2.0 includes additional tasks and additional motivational components and that the training interval was prolonged. The medium effect sizes are comparable to other trainings ( Kroesbergen and van Luit, 2003 ; Ise et al, 2012 ; Chodura et al, 2015 ) and are satisfactory for a sample of children with severe deficits (participants with DD).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It is assumed that the training leads to a higher automation of task processing resulting in faster fact retrieval. Compared to the evaluative studies regarding the previous version Calcularis 1.0 ( Käser et al, 2013a ; Rauscher et al, 2016 ; Kohn et al, 2017 ) the observed training effects are stronger, whereby it has to be considered that Calcularis 2.0 includes additional tasks and additional motivational components and that the training interval was prolonged. The medium effect sizes are comparable to other trainings ( Kroesbergen and van Luit, 2003 ; Ise et al, 2012 ; Chodura et al, 2015 ) and are satisfactory for a sample of children with severe deficits (participants with DD).…”
Section: Discussionmentioning
confidence: 83%
“…The virtual zoo allows children to buy and feed animals which can be assigned to various zoo worlds (Figure 1, bottom). Calcularis, the pre-version of Calcularis 2.0, was evaluated in children with mathematical difficulties as well as in normally achieving children (Käser et al, 2013a;Rauscher et al, 2016). The study results demonstrated that children benefited significantly from the training regarding spatial number representation and subtraction.…”
Section: Methodsmentioning
confidence: 99%
“…However, drill-practicing number knowledge without providing children with sufficient opportunities to understand how numbers represent non-symbolic magnitudes may be equally inefficient. Training programs should thus focus on understanding and efficiently processing symbolic representation of number, which entails to map them on their inborn nonsymbolic representational system (e.g., Kuhn and Holling, 2014;Rauscher et al, 2016). Improving our knowledge of longitudinal developmental trajectories and neurocognitive mechanisms of symbolic and arithmetic processing skills is necessary in order to further advance our understanding of the components that should be integrated in evidence-based tailored intervention programs.…”
Section: Resultsmentioning
confidence: 99%
“…Adaptive computing is highly relevant in the affective domain, as a study by Rauscher et al (2016) showed. They demonstrated that the adaptive training program Calcularis can be used effectively to support children with developmental dyscalculia or math difficulties in their numerical development and to enhance numerical cognition while reducing math anxiety by adapting to the children's strengths, down-powering frustrating experiences with arithmetics.…”
Section: The Power Of Gaming: Augmenting Neuroplasticity Through Crea...mentioning
confidence: 99%